Elastic properties of solids at high pressure - Vekilov, Y.; Krasilnikov, O.; Lugovskoy, Andrey (Turpion Ltd, 2015)
© 2015 Uspekhi Fizicheskikh Nauk, Russian Academy of Sciences.This review examines the elastic response of solids under load. The definitions of isothermal and adiabatic elastic constants of nth order (n=2) for a loaded crystal are given. For the case of hydrostatic pressure, two techniques are proposed for calculating the second-, third-, and fourth-order elastic constants from the energy-strain and stress-strain relations. As an example, using the proposed approach within the frame- work of the density functional theory, the second- to fourth- order elastic constants of bcc tungsten are calculated for the pressure range of 0-600 GPa.